The use of microbial-earthworm ecofilters for wastewater treatment with special attention to influencing factors in performance: A review. (January 2016) - Jiang, Luhua; Liu, Yunguo; Hu, Xinjiang; Zeng, Guangming; Wang, Hui; Zhou, Lu; Tan, Xiaofei; Huang, Binyan; Liu, Shaobo; Liu, Simian
Highlights: The application of MEEs for treatment of various wastewater has been reviewed. The environment-economic analysis of MEEs was given. The influencing factors of pollutants removal in MEEs have been provided and summarized. Future research was given on enhancing performance and sustainability of MEEs. Abstract: With the unique advantages of lower operational and maintenance cost, the use of microbial-earthworm ecofilters (MEEs) for the wastewater treatment has been increasing rapidly in the recent years. This paper provided an overview of the research activities on the use of MEEs for removing pollutants from various wastewater throughout the world. However, the long-term effective treatment performance and sustainable operation of this system still remain a challenge since the treatment performance would be affected by design parameters, operational conditions, and environmental factors. In order to promote the treatment performance, therefore, this paper also provided and summarized the influencing factors of pollutants removal in MEEs. The design parameters and operational conditions of MEEs include earthworm species and load, filter media type, hydraulic loading rate, nutrient load, packing bed height, chemical factors and temperature. Lastly, this review highlighted the further research on these issues to improve performance and sustainability of MEEs.